2011
DOI: 10.1111/j.1365-2710.2011.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the possible role of the essential fatty acids and fish oils in the aetiology, prevention or pharmacotherapy of schizophrenia

Abstract: Summary What is known and Objective:  Fish oils and other essential fatty acids have been purported to ameliorate the symptoms of schizophrenia or the adverse effects of the drugs that are used to manage it. Our objective is to review the basic and clinical evidence regarding replenishment of the reported decreased levels of polyunsaturated essential fatty acids, such as the omega‐3 docosahexaenoic acid, the omega‐6 linoleic and arachidonic acids, in brains of patients with schizophrenia. Methods:  We summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 65 publications
(155 reference statements)
0
16
0
Order By: Relevance
“…It is hoped that answers will rapidly emerge from this study. In schizophrenia and depression, there are several studies examining the effects of ingesting omega-3 fatty acids [43,146]. Potentially, ingestion of omega-3s or correction of an omega-6/omega-3 imbalance [43,147] can contribute to balancing the cholesterol system and alleviating psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that answers will rapidly emerge from this study. In schizophrenia and depression, there are several studies examining the effects of ingesting omega-3 fatty acids [43,146]. Potentially, ingestion of omega-3s or correction of an omega-6/omega-3 imbalance [43,147] can contribute to balancing the cholesterol system and alleviating psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the trials has been limited to 8–16 weeks in the majority of the studies. The main issue is that no conclusions could be drawn regarding the medium- to long-term effects of HUFAs in schizophrenia, according to the findings of the four meta-analysis available on this topic [25,26,27,28] (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Four meta-analyses [25,26,27,28] of RCTs were conducted in order to establish if the available data support the use of omega-3 fatty acids in patients affected by schizophrenia or other psychotic disorders. The authors concluded that the evidence in favor of omega-3s as psychotropic agents in schizophrenia is preliminary, and the findings remain yet inconclusive.…”
Section: Methodsmentioning
confidence: 99%
“…The results have been mixed: two recent literature reviews of clinical trials did not find statistical differences compared to placebo (Fusar-Poli and Berger, 2012; Akter et al, 2012); however, overall sample size was low, methodology was heterogeneous, and there were some positive effects. One other recent study showed beneficial effects of n-3 fatty acids on treatment and attenuating conversion to psychosis among high risk groups (Amminger et al, 2010), and several literature reviews have shown dose-responsive positive effects on cognition and vision with DHA and AA supplementation in the general population (SanGiovanni et al, 2000; Hoffman et al, 2009; Ryan et al, 2010).…”
Section: Mechanismsmentioning
confidence: 96%